Intensified wind pollination mediated by pollen dimorphism after range expansion in an ambophilous biennial Aconitum gymnandrum. Issue 2 (20th December 2016) - Wang, Lin‐Lin; Zhang, Chan; Yang, Ming‐Liu; Zhang, Guo‐Peng; Zhang, Zhi‐Qiang; Yang, Yong‐Ping; Duan, Yuan‐Wen
Abstract: Pollination systems and associated floral traits generally differ between core and marginal populations of a species. However, such differences are rarely examined in plants with a mixed wind‐ and bumblebee‐pollination system, and the role of wind pollination during range expansion in ambophilous plants remains unclear. We compared floral traits and the contributions of bumblebee and wind pollination in refugium and marginal populations of the ambophilous plant Aconitum gymnandrum . We found that most floral traits differed between the two populations, and those traits associated with the shift to wind pollination were pronounced in the marginal population. Bumblebee visitation rates varied significantly, but were generally low in the marginal population. Wind pollination occurred in both populations, and the efficiency was lower than that of bumblebee pollination. Two types of pollen grains, namely round and fusiform pollen, were transported to a stigma by bumblebees and wind, but fusiform pollen contributed to wind pollination to a larger degree, especially in the marginal population. Our results suggest that wind pollination was enhanced by pollen dimorphism in the marginal population of A. gymnandrum, and wind pollination may provide reproductive assurance when bumblebee activity is unpredictable during range expansion, indicating that ambophily is stable in this species and shift in pollination system could be common when plants colonize new habitats. Abstract : Our results suggested that wind pollination was enhanced by pollen dimorphism in the marginal population of Aconitum gymnandrum, and wind pollination may provide reproductive assurance when bumblebee activity is unpredictable during range expansion, indicating that ambophily is stable in this species.